2020
DOI: 10.1038/s41436-019-0722-8
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical utility of genetic testing in 201 preschool children with inherited eye disorders

Abstract: Purpose A key property to consider in all genetic tests is clinical utility, the ability of the test to influence patient management and health outcomes. Here we assess the current clinical utility of genetic testing in diverse pediatric inherited eye disorders (IEDs). Methods Two hundred one unrelated children (0–5 years old) with IEDs were ascertained through the database of the North West Genomic Laboratory Hub, Manchester, UK. The cohort was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 38 publications
3
44
1
Order By: Relevance
“…For RED, a significant number of patients have an underlying genetic etiology. Effective and individualized approaches to clinical management are consequently dependent upon a comprehensive means of delivering genetic or genomic testing [ 8 ]. Genomic testing allows a precise diagnosis of highly heterogeneous disorders, improves counselling (e.g.…”
Section: Main Textmentioning
confidence: 99%
“…For RED, a significant number of patients have an underlying genetic etiology. Effective and individualized approaches to clinical management are consequently dependent upon a comprehensive means of delivering genetic or genomic testing [ 8 ]. Genomic testing allows a precise diagnosis of highly heterogeneous disorders, improves counselling (e.g.…”
Section: Main Textmentioning
confidence: 99%
“…The clinical exome (Oculome) does not search for CNVs nor have they yet been analyzed by the Genomics England analysis pipeline. Molecular diagnostic rates for albinism are highly variable, ranging from 56–91% in the literature [ 32 , 53 , 54 ]. Lasseaux et al (2018) reported a diagnostic yield of 72% from a large French study of 990 probands with albinism [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Lenassi et al solved 29 out of 32 (91%) preschool children with suspected albinism using a targeted panel of 18 ( n = 30) or 26 ( n = 1) or 40 ( n = 1) genes with confirmed mutations in TYR ( n = 18), OCA2 ( n = 7), TYRP1 ( n = 2), HPS5 ( n = 1), and GPR143 ( n = 1). The authors did not specify the reason for selecting different gene-specific panels and the patient demographic details (aside from age) were not presented [ 54 ]. The probands who underwent expanded gene panel testing harbored OCA2 and TYR variants.…”
Section: Discussionmentioning
confidence: 99%
“…These included gathering further phenotypic details from the family and initiating additional clinical work-up to further investigate the patient's phenotype. In a cohort of 201 preschoolers with inherited eye disorders, medical records were reviewed to identify that unnecessary diagnostic tests were avoided in 21% of patients, as a result of genetic or genomic testing 33 .…”
Section: The Fryback and Thornbury Model Applied To Evidence Collectimentioning
confidence: 99%